2020
DOI: 10.3390/cancers12071784
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemistry-Based Taxonomical Classification of Bladder Cancer Predicts Response to Neoadjuvant Chemotherapy

Abstract: Background: Platinum-based neoadjuvant chemotherapy (NAC) increases the survival of patients with organ-confined urothelial bladder cancer (UBC). In retrospective studies, patients with basal/squamous (BASQ)-like tumors present with more advanced disease and have worse prognosis. Transcriptomics-defined tumor subtypes are associated with response to NAC. Aim: To investigate whether immunohistochemical (IHC) subtyping predicts NAC response. Methods: Patients with muscle-invasive UBC having received plat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 36 publications
1
25
0
1
Order By: Relevance
“…A recent study by our group, using IHC-based hierarchical clustering, classified MIBC patients treated with NAC in three clusters: BASQ-like (FOXA1/GATA3 low; KRT5/6/14 high), luminal-like (FOXA1/GATA3 high; KRT5/6/14 low), and mixed-cluster (FOXA1/GATA3 high; KRT5/6 high; KRT14 low). Patients with BASQ-like tumors were more likely to achieve a pathological response to NAC (OR 3.96; p = 0.017) [ 36 ].…”
Section: Therapeutic Implications Of Bc Molecular Subtypesmentioning
confidence: 99%
“…A recent study by our group, using IHC-based hierarchical clustering, classified MIBC patients treated with NAC in three clusters: BASQ-like (FOXA1/GATA3 low; KRT5/6/14 high), luminal-like (FOXA1/GATA3 high; KRT5/6/14 low), and mixed-cluster (FOXA1/GATA3 high; KRT5/6 high; KRT14 low). Patients with BASQ-like tumors were more likely to achieve a pathological response to NAC (OR 3.96; p = 0.017) [ 36 ].…”
Section: Therapeutic Implications Of Bc Molecular Subtypesmentioning
confidence: 99%
“…A recent study which classified molecular subtypes by IHC on TMA-cores only, reported improved chemotherapy response and survival in patients with basal/squamous-like tumors. 13 However, this study included an unknown proportion of carboplatin-based regimens, 17% clinically node-positive patients, and did not report any survival data adjusted for clinical tumor stage. This study used nearly identical markers for the basal/squamous-like subtype as used in the LundTax IHC subtyping.…”
Section: Discussionmentioning
confidence: 99%
“…Varying response to systemic treatments in molecular subtypes has been suggested by previous studies but with disparate results. [9][10][11][12][13][14] In addition, genomic alterations in DNA repair genes such as ERCC2 mutations [15][16] and ATM, RB1 or FANCC mutations 17 have been associated with improved response to neoadjuvant chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…The interplay between bladder tumour biology, chemotherapy response and resistance mechanisms are complex. Recently, it has been suggested molecular subtyping may impact patient benefit to NAC [20][21][22][23]. Molecular subtypes have been discovered that are associated with specific clinicopathological characteristics and differential sensitivity to treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, identification of a reliable method to stratify NAC administration based on predicted response is of critical importance for the management of MIBC patients and may ultimately lead to future personalised medicine. Recent studies have explored DNA repair gene mutations (ERCC1, ERCC2, BRCA1) [9][10][11][12], regulators of apoptosis (survivin, Bcl-xL) [13], receptor tyrosine kinase mutations (ERBB2) [14], gene expression signatures [13,[15][16][17][18][19], molecular subtypes of bladder cancer [20][21][22][23] and alterations in the cellular mechanisms of drug uptake/transport (CTR-1, MDR1) [24,25] as potential predictors of response to NAC and offer promise for improving patient selection for such treatment and clinical outcomes. However, to date, no biomarker exists in the clinical setting to prospectively identify the patients most likely to benefit from NAC.…”
Section: Introductionmentioning
confidence: 99%